The Mid-Victorian economy making, earning and spending in Britain in - Feinstein, Charles H. 1932-2004 (Cambridge University Press, 2016)
This economic history of 1850s Britain gives an accurate account of the state of industry, output and consumption providing a benchmark for future comparative work by economists and economic historians. As a robust quantitative record, this will become a standard work of reference on the Victorian economy